2000
DOI: 10.1103/physrevlett.84.3322
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Fully Noninductive Current Driven by Electron Cyclotron Waves in a Magnetically Confined Plasma

Abstract: A steady-state, fully noninductive plasma current has been sustained for the first time in a tokamak using electron cyclotron current drive only. In this discharge, 123 kA of current have been sustained for the entire gyrotron pulse duration of 2 s. Careful distribution across the plasma minor radius of the power deposited from three 0. 5-MW gyrotrons was essential for reaching steady-state conditions. With central current drive, up to 153 kA of current have been fully replaced transiently for 100 ms. The noni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 11 publications
2
41
0
Order By: Relevance
“…Extensive studies on DIII-D have shown that the experimentally measured EC driven current is in good agreement with predictions from combined ray-tracing and FokkerPlanck code calculations provided the synergy between the ECCD and a residual parallel electric field is properly accounted for [31]. Full non-inductive current drive over several current diffusion times has been demonstrated on TCV [32]. In these discharges, the EC driven current density profile had to be carefully tailored in order to avoid driving too much current near the centre of the discharge and the resulting instabilities.…”
Section: Iiib Electron Cyclotron Current Drive (Eccd)mentioning
confidence: 63%
“…Extensive studies on DIII-D have shown that the experimentally measured EC driven current is in good agreement with predictions from combined ray-tracing and FokkerPlanck code calculations provided the synergy between the ECCD and a residual parallel electric field is properly accounted for [31]. Full non-inductive current drive over several current diffusion times has been demonstrated on TCV [32]. In these discharges, the EC driven current density profile had to be carefully tailored in order to avoid driving too much current near the centre of the discharge and the resulting instabilities.…”
Section: Iiib Electron Cyclotron Current Drive (Eccd)mentioning
confidence: 63%
“…At high enough power, the plasma temperature is high and the transport effects strong enough such that radial transport dominates the collisional slowing down time of the fast electrons. Our calculations [8] show that this is strongly the case for a representative full-toroidal-current-drive electron cyclotron current drive (ECCD) experiment [9] in the TCV fusion energy tokamak. Although there is little doubt as to whether plasma turbulence is responsible for the observed radial transport in excess of collisional levels [10], questions remain on the extent electrostatic (ES) or magnetic turbulence dominates [11] and also the degree of concurrence between tail electron transport and bulk plasma transport.…”
mentioning
confidence: 98%
“…We examine the TCV shot 16099 which is fully supported by EC current drive [9]. The EC ray geometry is shown superimposed on a cross-section of the toroidal flux surfaces in Fig.…”
Section: Rw Harvey Et Al Radial Transport Effects On Eccd In the mentioning
confidence: 99%
“…The electron cyclotron resonance heating (ECRH) has shown several advantages from plasma start-up to MHD control in various tokamaks [1][2][3][4][5][6][7][8][9]. The 42GHz/500kW ECRH system is used in tokamak SST-1 [10] to carry out experiments related ECRH assisted breakdown and start-up at fundamental and second harmonic.…”
Section: Introductionmentioning
confidence: 99%